Notícia sobre vaso grego destinado ao transporte e conservação de mel - Morais, Rui (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In recent years we have been making known the existence of pots for the transportation of honey used since early epochs of humankind. In this paper we reveal the existence of a Greek vase of Italiote production from Tarcentum (northeast Italy), which is now part of the collection of the Michigan University Museum and was very probably used to transport this product. We also put forward that these type of containers can go back to the earliest civilizations, namely from Mesopotamia.